PEDAGOGICAL PROBLEMS OF FORMING MUSIC-THEORETICAL LITERACY IN STUDENTS IN MUSIC LESSONS - Sayfiddinov Muhriddin (Bright Mind Publishing, 2025)
The article analyzes pressing issues encountered in the process of developing students’ musical theoretical literacy in music culture classes at general secondary schools. Particular attention is given to the close integration of musical theoretical knowledge with practical performance activities, as well as to the consideration of students’ age-related and psychological characteristics. In addition, the effectiveness of traditional and modern pedagogical approaches in enhancing musical literacy is examined.
Keywords: Musical-theoretical literacy, music culture classes, pedagogical issues, teaching methods, musical thinking, didactic tools.